Strategi Pengembangan Usaha Melalui Business Model Canvas (Studi Kasus "JW Roti" Di Desa Totolan Kecamatan Kakas Barat Kabupaten Minahasa) - Walean, Jovanka Jermias Rivaldo; Pangemanan, Paulus Adrian; Lolowang, Tommy Fredy (AGRI-SOSIOEKONOMI, 2023)
This study aims to evaluate the business model applied at "JW Roti" with the Business Model Canvas approach and establish a business strategy for the "JW Roti" business in Totolan Village. This research will be carried out from January 2022 to March 2022 in the "JW Roti" business in Totolan Village, West Kakas District, Minahasa Regency. The data collected in this study are primary data and secondary data originating from the internal and external environment. Primary data was obtained from internal parties, namely the owner of "JW Roti" and its employees and external parties, namely consumers of "JW Roti" while secondary data was obtained from agencies related to the research conducted. Sampling was carried out by direct observation, interviews and documentation at "JW Roti". From the results of the research conducted, it can be concluded that the Business Model Canvas concept implemented by "JW Roti" includes (1) Customer segment, not distinguishing between customers; (2) Value Propositions (VP), producing new variants; (3) Channels, customers buy directly in stores; (4) Customer Relationship, implementing personal assistance relationships; (5) Revenue Streams, income through transactions; (6) Key Resources, land and buildings for production; (7) Key Activities, bread making; (8) Key Partnerships, suppliers of raw materials; and (9) Cost Structure, fixed costs and variable costs.